PENGARUH REBUSAN DAUN ALPUKAT TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI: SYSTEMATIC REVIEW - Alifariki, La Ode (NHM PRESS, 2024)
Hypertension is one of the most common cardiovascular diseases and is the number 1 killer, so it needs treatment and prevention. Treating patients with natural ingredients can reduce family expenses and reduce the impact or negative effects of chemical treatments. The final results were collected as many as 13 articles that met the inclusion criteria. Various research results in this study provide a similar picture, namely a decrease in systolic and diastolic blood pressure after administering boiled avocado leaves.